Postoperative JJ stent is not necessary after balloon high-pressure endoscopic dilatation of primary obstructive megaureter. Issue 3 (June 2022) - Faraj, Sebastien; Loubersac, Thomas; Graveleau, Aurelien; Alliot, Hortense; Camby, Caroline; Leclair, Marc-David
Summary: Introduction: A wide range of surgical interventions have been described for the management of primary obstructive megaureter (POM). Endoscopic balloon dilatation has been developed through last decades as a minimally invasive alternative to classic surgery. Objective: To assess the need for placement of a double J stent after endoscopic balloon dilatation procedure, by comparing the post-operative related outcomes with and without double J placement. Secondary outcome was the success rate, considering the need for further procedure after endoscopic balloon dilatation and the improvement of the ureteral diameter in the two groups. Study design: Historical retrospective comparison of children treated by endoscopic dilatation for POM, with post-operative JJ stent left in place (2012–2014) or without ureteral JJ stent (since 2015). Post-operative complications were reported following Clavien-Dindo grading system and compared between the two groups. Success rate was defined as absence of need for further surgical reimplantation. Ureteral diameters on preoperative and postoperative renal ultrasounds were compared. Results: Endoscopic dilatations were performed in 42 patients for 46 renal units during the study period. There was a significantly higher rate of post-operative complications in the group with JJ stenting compared to the group without double J stenting regarding all Clavien-Dindo grades (56% vs 15%, p = 0.014) and Clavien-Dindo grade III only (31% vs 0%, p = 0, 0051) (Figure). The success rate was similar in the JJ group (75%, F-up: 70 months [13–101]) and the no JJ group (81%, F-up: 26 months [12–95]). There was a significant improvement of US renal pelvis and ureter dilatation in both groups, with a median follow-up of 35.5 months [12–101]. Discussion: The overall rate of complications was slightly higher than in other reports and higher in the JJ group regarding Clavien-Dindo grade III complications. The success rate was comparable to previous studies reviewing endoscopic dilatations and equivalent in the two groups. Conclusion: In our study, the omission of postoperative ureteral drainage by a JJ stent after endoscopic balloon dilatation of POM did not increase post-operative complications rate without demonstrable impact on the success rate. Summary Figure Comparison of post-operative related complications following Clavien-Dindo grading system Summary Figure